Manajemen Kepemimpinan Era Digital: Konsep, Gaya dan Pengembangan Kepemimpinan pada Generasi Milenial dan Z - Indra Permana; Ilmi Gunardi; Bayu Tri Pratomo; Muhamad Zaenal Arifin; Imam Kurnianto (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The purpose of writing this article is to empirically describe leadership in the digital era from the concept, style and development aspects of leadership in the millennial and Z generations. The research method is library research. So researchers look for relevant scientific articles from Science Direct and Google Scholar by including the keywords digital era leadership, millennial generation and Z generation to support thoughts and ideas. The data were then analyzed descriptively to be combined with other findings in the study. Results: (1) Digital leadership is an interactive relationship between leaders and members of the organization that is carried out remotely by using digital media so that there is no need for face-to-face meetings that provide freedom of space and time, digital platforms, organizational leaders can easily monitor in real time. Virtual leaders are leaders who direct people remotely to do work to achieve organizational goals. They use new technologies to improve their work, to discover new business models, to communicate with their followers. The challenge of E-Leaders is that without face to face it is very difficult to build trust with followers in virtual communication. E-Leader competency development by always being updated with developments in information and communication technology.